PELATIHAN DIGITALISASI LAYANAN POSYANDU DENGAN SEHATLINK UNTUK PEMANTAUAN KESEHATAN KELUARGA KELURAHAN RAGUNAN - Putri, Sukmawati Anggraeni; Kristiana, Titin; Setiaji, Setiaji (LPPM Universitas Nusa Mandiri, 2025)
Posyandu plays a crucial role in promotive and preventive health efforts, particularly in stunting prevention and early detection of chronic diseases, yet challenges remain in data recording and information dissemination. This community service activity aimed to enhance cadre capacity and community participation through digitalizing services using the SehatLink website. The program involved 24 cadres from Posyandu RW 01 Ragunan Village, employing training, technical assistance, and pre-test and post-test evaluations. Results showed significant improvements in cadre management aspects: digital training needs increased by 74%, perceived effectiveness of the application in stunting prevention reached 83%, trust in digital data rose to 80%, and support for data-based decision making reached 81%. Among the community, understanding of healthy eating patterns increased by 73%, effectiveness of digital education by 85%, ease of access to health information by 78%, and family involvement in health monitoring by 73%. These findings confirm that SehatLink effectively strengthens cadre capacity and enhances community engagement in digital health services, especially for stunting prevention and early detection of chronic diseases. Program sustainability requires ongoing training, development of contextual educational content, and integration into regional health information systems.